2016
DOI: 10.1039/c5cp06914a
|View full text |Cite
|
Sign up to set email alerts
|

Controllable defluorination of fluorinated graphene and weakening of C–F bonding under the action of nucleophilic dipolar solvent

Abstract: The effect of solvent on the chemical structure and properties of fluorinated graphene (FG) was particularly investigated in this work. It is found that the reduction of FG and the weakening of strong covalent C-F bonding take place under the action of some dipolar solvents even at room temperature. The rate of the C-F bond rupture reaction is positively influenced by the dipole moment of solvent and fluorine coverage of FG sheets. Meanwhile, defluorination of FG is controllable through the time and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…[27] However, the scope of our work is fundamentally different as we focus on CVD graphene with systematic investigation and characterization, and more importantly, demonstrate an exciting new strategy to exploit the solvents as a tool for the fabrication of unprecedentedly high resolution lateral 2D heterostructures on continuous films for their use in high performance optoelectronic devices (as discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…[27] However, the scope of our work is fundamentally different as we focus on CVD graphene with systematic investigation and characterization, and more importantly, demonstrate an exciting new strategy to exploit the solvents as a tool for the fabrication of unprecedentedly high resolution lateral 2D heterostructures on continuous films for their use in high performance optoelectronic devices (as discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…Note that unlike DMAc,t hese solvents did not lead to severe defluorination of FG. [13] Figure2(b) shows the UV/Vis spectra of re-dispersions of FG-PBA prepared in theses olvents and their corresponding reaction efficiencies (h). Herein, the reaction efficiency is defined as the ratio of the calculated content of covalently bonded PBAo ng raphene based on the standard curve of PBA (see Figure S1 in the Supporting Information) to its actual addition prior to reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] It is also shown that the defluorination can be achieved by exposing FG to ultraviolet irradiation for long time in aromatic solvents like toluene and benzene. 23,41 On a different report, the possibilities of defluorination by the solvent based treatment of fluorinated graphene is also discussed, where the semi-ionic C-F bonds were removed from fluorinated graphene upon its treatment with dipolar solvents such as N-methyl-2-pyrrolidinone (NMP) via ultra-sonication. 23 Recently, the authors have demonstrated that the interactions between polar solvents and C-F bond in FG are highly crucial for the solvent assisted defluorination, and even moderately polar solvents such as tetrahydrofuran (THF) can interact with FGO to remove C-F bonds in a day or two without any extensive sonication.…”
Section: Fluorination Of Graphene-synthesis and Control Of Fluorinementioning
confidence: 99%